In-vitro comparison of antibacterial activities on stingless bee propolis using selected extraction methods / Osamah Hasan Hamood Al-Masoodi ... [et al.] - Hamood Al-Masoodi, Osamah Hasan; Said Gulam Khan, Hasnah Begum; Baharuddin, Izyan Hazwani; Ismail, Ikmal Hisham (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
This study aimed to compare the different selected extraction methods of propolis extracts against Enterococcus faecalis (E. faecalis). Extraction of Malaysian Propolis (MP) from Heterotrigona itama, was carried out using 70% ethanol. For the selected extraction processes, such as, centrifugation-assisted extraction (CAE), vacuum-assisted extraction (VAE), and shaking-assisted extraction (SAE) methods were used. Antimicrobial activity against E. faecalis was assessed using the antibacterial susceptibility test (AST). The results showed that SAE, followed by CAE, had better antimicrobial properties as compared to those obtained by VAE. The inhibition zones for SAE, CAE, and VAE were 5.3mm, 4.67mm, and 4.16mm, respectively. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for extracted MP by SAE were 12.5 and 25 mg/mL, respectively. Furthermore, non-setting calcium hydroxide’s [Ca(OH)2 ] MIC and MBC were determined to be 50 and 100 mg/mL, respectively. As a result, we believe that extraction of raw MP from Heterotrigona itama using the SAE method was more effective than Ca(OH)2 against E. faecalis.